Experimental usage of a multicomponent film in treatment of wounds - A. Yu. Grigoryan; A. I. Bezhin; T. A. Pankrusheva; B. S. Sukovatykh; M. S. Chekmareva; L. V. Zhilyaeva (Бюллетень сибирской медицины, 2019)
Objectives. To optimize treatment of purulent wounds with the help of a wound coating with a multidirectional action that combines broad-spectrum antimicrobial effect, stimulation of regeneration, sorption activity and local anesthetic action. Materials and methods. The material for the study was a wound covering in the form of a film developed by the authors at Kursk State Medical University (Russian patent No. 2601897). Theexperiment was performed on laboratory animals (Wistar rats), which were divided into 2 groups (comparison and experimental), each group containing 36 animals. Purulent wound was modeled in the animals according to the method of P.I. Tolstykh. To evaluate the effectiveness of the treatment, the following methods were used: microbiological method (determination of areas of growth retardation and bacterial contamination in the wounds), Renier’s method (determination of local anesthetic activity), visual assessment of wounds, planimetric method (measurement of the wound area, percentage of area reduction and healing speed) and measurement of pH in the wounds. The statistical significance of the differences was determined with the nonparametric Mann–Whitney test. The differences were considered statistically significant at p ˂ 0.05. Results. Initially, high efficiency of the film was detected in vitro for the most common strains of test organisms, which werewound infection pathogens. The Renier index was 1.2 times higher in the film with chlorhexidine than in 2% lidocaine ointment, and the duration of general anesthesia was 25% longer. Following visual assessment of the wounds we revealed that purification and regeneration of the wounds first occurred in the animals in the experimental group; however, no statistical significance was detected. The maximal differences in the healing speed (1.6 times) were observed at 3–5 days, and the contamination of the wounds was 1.3 times lower in the experimental group than in the comparison group. According to the results of pH assessment, significant differences between the groups were noted only on day 15. Approximation of pH values to intact skin values also proved the effectiveness of treatment. Conclusion. The developed contact wound covering has high antimicrobial activity against a broad spectrum of wound infection pathogens, creates a fairly good local anesthetic effect, significantly speeds up the healing process and reduces bacterial contamination of the wound area. Thus, the developed wound covering can be recommended for further studies in the clinical setting for treatment of inflammatory processes in soft tissues.